Examining the Effects of Smart Destination Management on Tourists’ Satisfaction and Perceived Sustainability in Indonesia: A Structural Equation Model - Khalik, Wahyu; Aini, Yulis Nurul; Azizurrohman, Muhammad (STI Policy and Management Journal, 2025)
This study examines the influence of smart destination management on tourists’ satisfaction and perceived sustainability in six major destinations in Indonesia: Jakarta, Bandung, Yogyakarta, Malang, Bali, and Lombok. Using the Smart Tourism Destination (STD) framework, this study investigates the effects of smart tourism infrastructure, destination communication, and crowd management experience, with perceived destination accessibility as a mediator and tourists’ digital literacy as a moderator. A total of 380 valid responses were collected through a structured survey and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that the three core dimensions contribute significantly to enhance tourists’ satisfaction, with perceived accessibility serving as key mediator. Tourists’ satisfaction also strongly predicts perceived sustainability. Digital literacy moderates the smart services’ effectiveness, highlighting the importance of individual readiness. Multi-Group Analysis (MGA) results reveal that crowd management has a significantly stronger impact in islandbased destinations, suggesting the need for context-sensitive strategies. Theoretically, this study expands the STD framework by integrating individual and spatial dimensions. Practically, it offers insights for destination managers to invest in inclusive technologies, support digital literacy, and tailor approaches based on destination types. These findings support the development of smart and sustainable tourism, particularly in emerging economies like Indonesia.